2000
DOI: 10.1002/1521-2254(200011/12)2:6<395::aid-jgm146>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid vector designs to control the delivery, fate and expression of transgenes

Abstract: One of the greatest challenges to gene therapy is the targetting of gene delivery selectively to the sites of disease and regulation of transgene expression without adverse effects. Ultimately, the successful realization of these goals is dependent upon improvements in vector design. Over the years, viral vector design has progressed from various types of replication-defective viral mutants to replication-conditioned viruses and, more recently, to 'gutted' and hybrid vectors, which have, respectively, eliminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 150 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…Based on the local, non‐metastatic growth pattern of gliomas, gene therapy has been considered as a possible new approach for the treatment of these tumors. Vector systems used in gene therapy for gliomas include replication‐defective retroviruses, adenoviruses (Ad), herpes simplex viruses (HSV) and hybrid vectors derived from them 3, 4, 5, 6, 7, 8, 9, 10. These vectors have been used to deliver a therapeutic (suicide) gene expressing e.g.…”
mentioning
confidence: 99%
“…Based on the local, non‐metastatic growth pattern of gliomas, gene therapy has been considered as a possible new approach for the treatment of these tumors. Vector systems used in gene therapy for gliomas include replication‐defective retroviruses, adenoviruses (Ad), herpes simplex viruses (HSV) and hybrid vectors derived from them 3, 4, 5, 6, 7, 8, 9, 10. These vectors have been used to deliver a therapeutic (suicide) gene expressing e.g.…”
mentioning
confidence: 99%
“…Development of viral vectors allowing for a long-term expression 25,26 combined with a targeted delivery and/or cell-specific expression of therapeutic proteins 27,28 will allow to increase the level of antibody production while reducing the vector and transgene-associated toxicity. In addition, the combination of antiangiogenic therapy using recombinant adenoviruses encoding scFv V65 and its derivatives and radio-or low-dose chemotherapy, which proved to be beneficial for other antiangiogenic drugs, [29][30][31] can be a useful strategy to improve the performance of the anti-VEGF scFv.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials showed that these vectors have some inherent limitations for therapy, namely, immunogenicity, toxicity, limited loading capacity, and failure of long-term adequate transgene expression. To overcome these drawbacks, attempts have been made, in order to combine the best characteristics of different viruses, by means of hybrid vectors [69].…”
Section: Hybrid or Chimeric Vectorsmentioning
confidence: 99%